Edukasi Gizi Seimbang bagi Bumil, Bayi, Balita dengan Akupresure dan Babby Massage - Maria Beata Aku; Helena Petra Bui; Raquela Das Dores; Etilia Abuk; Soeyono, Dwi; Heni Hirawati Pranoto (Universitas Ngudi Waluyo, 2024)
Suboptimal nutritional conditions are related to health problems and poor health conditions and increase the risk of infectious and non-communicable diseases. Optimal nutrition is very important for normal growth and physical development of babies, toddlers and pregnant women. One non- pharmacological way to increase a child's appetite is through massage/touch. This massage is best done by the child's parents themselves, because apart from getting physical benefits from massage, it is also able to increase bonding between parents and children. Massage can improve blood circulation in the spleen and digestion, through modification of acupuncture points without needles. Based on the results of the study carried out from 20 to 25 May 2024, several problems were found, including nutritional problems in pregnant women, babies and toddlers. There were 2 pregnant women with mild anemia, there were also 10 babies under five with malnutrition and 4 with stunting. So there is a need for education about complementary care for pregnant women and toddlers. The evaluation results according to the pre and post-test assessments showed that the majority of mothers had increased knowledge (85%) after the education was carried out. Abstrak Kondisi gizi yang tidak optimal berkaitan dengan gangguan Kesehatan dan kondisi Kesehatan yang buruk serta meningkatkan risiko penyakit infeksi dan penyakit tidak menular. Gizi yang optimal sangat penting untuk pertumbuhan normal serta perkembangan fisik bayi, balita maupun ibu hamil. Salah satu cara non farmakologi untuk meningkatkan nafsu makan anak adalah melalui pijat/ sentuhan. Pijat ini sangat baik dilakukan oleh orang tua anak itu sendiri, karena selain mendapatkan manfaat fisik dari pijat, juga mampu meningkatkan bonding antara orang tua dan anak. Pijat dapat memperlancar peredaran darah pada limpa dan pencernaan, melalui modifikasi dari titik akupuntur tanpa jarum. Berdasarkan hasil pengkajian yang dilakukan tanggal 20 hingga 25 Mei 2024 ditemukan beberapa masalah, diantaranya terdapat masalah gizi pada ibu hamil, bayi dan balita. Terdapat 2 ibu hamil dengan anemia ringan, terdapat juga 10 bayi balita dengan gizi kurang dan buruk serta 4 dengan stunting. Maka perlu adanya edukasi tentang asuhan komplementer pada ibu hamil, dan bayi balita. Hasil evaluasi menurut penilaian pre dan posttes diketahui sebagian besar ibu memiliki pengetahuan yang meningkat (85%) setelah dilakukan edukasi.